STRATEGI PENGEMBANGAN OBYEK WISATA TALANGINDAH BUKIT PANGONAN DI KABUPATEN PERINGSEWU PROVINSI LAMPUNG - Abrian Rafsanjani; Kuncoro G. Pambayun (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2018)
Talangindah Bukit Pangonan is one of nature tourism as well as historical tour owned by Pringsewu Regency. Now in the development stage to realize the dream tour for the tourists. But in recent years visitors who come to tourist sites have decreased. It is the responsibility of Pringsewu Regency Government to formulate strategy in developing tourism object of Talangindah Bukit Pangonan.The purpose of this writing is to formulate strategy in developing tourism object of Talangindah Bukit Pangonan. Apprenticeship method that writer use is qualitative explorative method with inductive approach. Data analysis techniques using SWOT analysis techniques, namely formulating strategies using internal and external factors. The result is Strategy that can be done to develop Tourism Object Talangindah Bukit Pangonan is to add new tour package Trail Adventure; adding educational tours; and make the pond as a place of fishing; install road signs; increase community participation; to make regional regulations related to regional revenue in tourism objects; hold cultural attractions; complete the missing facilities; and discipline merchants. Keywords: strategy, development, tourism object